Cytotoxicity on MCF7 cell lines exposed to an extract of the jacalin from jackfruit seed - M.A., Zuraidah; Akbar John, B.; Yunus, Kamaruzzaman (Zibeline International Publishing Sdn. Bhd, 2017)
Jacalin is a major lectin present in jackfruit seeds, obtained by crude protein recovery. Its lectin symbol is AIL and it belongs to the galactose family of N-acetylglucosamine binding lectins, which are recognized to be cancer cell inhibitor. There have been many pharmacological research studies focusing intensively on jacalin, however their scope was restricted to the application of jacalin in pharmacology. Jacalin or lectin extract from jackfruit seed were induced cell cycle arrest in human breast cancer cell, MCF7, in comparison of crude extract, purified jacalin and jacalin standard. IC50 for MCF7 was achieved at concentration 125 µg/mL, comparable to jacalin standard with only 1.60 % contradictions.